THE ROLE OF TEACHERS IN IMPROVING STUDENTS' DIGITAL LITERACY IN THE GLOBALIZATION ERA: SYSTEMATIC LITERATURE REVIEW (SLR) - Aprilia Erin Chairunisa; Rizki Dwi Juliana; Titin Widi Astuti (Penelitian dan Pengembangan Ilmu, 2025)
This article examines the role of teachers in improving students' digital literacy in the era of globalization using the methodSystematic Literature Review(SLR) and PRISMA. Teachers play a central role as facilitators, mentors, and role models in fostering students' digital literacy, which includes the ability to use technology positively, evaluate information, communicate online, and understand the ethics and social implications of technology. The importance of this teacher role is also emphasized in the context of achieving the Sustainable Development Goals (SDGs). However, the development of digital literacy faces various challenges, such as limited access to technology, a lack of teacher and student competency in utilizing digital media, a curriculum that does not fully support it, and digital security threats such ascyberbullyingStrategies to address these challenges include providing engaging digital learning resources, enhancing teacher training in technology proficiency, and collaborating with schools, parents, and the community. Overall, digital literacy is an essential competency for students in the era of globalization. Therefore, teachers are required to continuously adapt and develop their competencies to prepare students to become digitally literate, critical thinkers, and responsible individuals.